Is Skin Color a Marker for Racial Discrimination? Explaining the Skin Color–Hypertension Relationship - Klonoff, Elizabeth A.; Landrine, Hope (Journal of behavioral medicine, 2000)
It is widely assumed that dark-skinned Blacks have higher rates of hypertension than their lighter-skinned cohorts because the former experience greater racial discrimination. However, there is no empirical evidence linking skin color to discrimination. This study tested the extent to which skin color is associated with differential exposure to discrimination for a sample of 300 Black adults. Results revealed that dark-skinned Blacks were 11 times more likely to experience frequent racial discrimination than their light-skinned counterparts; 67% of subjects reporting high discrimination were dark-skinned and only 8.5% were light-skinned. These preliminary findings suggest that skin color indeed may be a marker for racial discrimination and highlight the need to assess discrimination in studies of the skin color-hypertension relationship.